Activity of Microbial-Derived Phenolic Acids and Their Conjugates against LPS-Induced Damage in Neuroblastoma Cells and Macrophages - Dolores González de Llano; Mikel Roldán; Laura Parro; Begoña Bartolomé; M. Victoria Moreno-Arribas (Metabolites, 2023)
The aim of this study was to investigate whether microbial-derived phenolic acids, 3,4-dihydroxyphenylacetic (DHPA), protocatechuic acid (PCA), and dihydrocaffeic acid (DHCFA) and their conjugated forms (DHCFA 3-O-sulfate and DHCFA 3-O-β-D-glucuronide), exhibit protective effects against neuroinflammation and oxidative stress. Experiments were performed on human neuronal SH-SY5Y cells stimulated with bacterial lipopolysaccharide (LPS) and tert-butyl hydroperoxide (tBHP). Anti-inflammatory activity in terms of pro-inflammatory cytokine production was also evaluated in LPS-stimulated RAW 264.7 macrophages as a reactive microglial model. Treatment of the SH-SY5Y cells with the free phenolic acids, as well as with the conjugated metabolites, at physiologically concentrations (1, 10 and 50 μM), resulted in increased cell viability of LPS- and tBHP-stimulated cells. Phenolic metabolites and, especially, the conjugated derivatives also protected neuronal cells through significant attenuation of inflammation by decreasing ROS levels. Furthermore, the conjugated and microbial-derived phenolic metabolites significantly inhibited the secretion of proinflammatory cytokines (TNF-α, IL-6, and IL-8) in LPS-stimulated macrophages. Among the phenolic metabolites tested, different efficacies were observed, with the glucuronide form standing out. Overall, these results suggest, for the first time, that conjugated derivatives of phenolic acids seem to be more effective at protecting neurons from inflammation damage and oxidative stress. Further in vivo studies are warranted.